The Role of Molecular Modeling in TiO2 Photocatalysis - Cinar, Zekiye (MDPI, 2017)
Molecular Modeling methods play a very important role in TiO2 photocatalysis. Recent advances in TiO2 photocatalysis have produced a number of interesting surface phenomena, reaction products, and various novel visible light active photocatalysts with improved properties. Quantum mechanical calculations appear promising as a means of describing the mechanisms and the product distributions of the photocatalytic degradation reactions of organic pollutants in both gas and aqueous phases. Since quantum mechanical methods utilize the principles of particle physics, their use may be extended to the design of new photocatalysts. This review introduces molecular modeling methods briefly and emphasizes the use of these methods in TiO2 photocatalysis. The methods used for obtaining information about the degradabilities of the pollutant molecules, predicting reaction mechanisms, and evaluating the roles of the dopants and surface modifiers are explained.
Keywords: TiO2; photocatalysis; DFT; quantum mechanics; molecular modeling; N-DOPED TIO2; VISIBLE-LIGHT ACTIVITY; SOL-GEL METHOD; SURFACE MODIFICATION; HETEROGENEOUS PHOTOCATALYSIS; TITANIA PHOTOCATALYSTS; AROMATIC-SUBSTITUTION; HYDROXYL RADICALS; ASCORBIC-ACID; DEGRADATION; Biochemistry & Molecular Biology; Chemistry